IMPLICATIONS OF THE EXISTENCE OF FOREIGN WORKERS ON EFFORTS TO REALIZE JUSTICE AND WELFARE INDONESIAN WORKFORCE - Saut Tambunan; Otom Mustomi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
The problem of Foreign Workers in Indonesia is Foreign Workers who work in the industrial and infrastructure sectors that do not require special skills, so their presence has an impact on reducing job opportunities for local workers. The entry of foreign workers into Indonesia is also inseparable from the visa- free policy issued by the government. The policy on visa-free visits for 169 countries and the implementation of the ASEAN Economic Community (AEC), this policy makes the gates of Indonesia wide open for foreigners entering and exiting Indonesia. The fact is that what happens in the field is that many foreigners abuse this visa-free visit policy and many of them not only travel but work in Indonesia by taking advantage of the visa-free visit, if foreigners want to work in Indonesia the foreigner must use a work visa, not only that this visa- free visit policy causes many problems ranging from reduced state revenue, domestic security, order, and labor issues. This study aims to know, analyze and explain the government's supervision system over the policy of using Foreign Workers in Indonesia as stipulated in Law Number 6 of 2023 concerning the Stipulation of Perpu Number 2 of 2022 concerning Job Creation into Law, and aims to find out the implications of the existence of Foreign Workers on efforts to improve justice and welfare of Indonesia's workforce. The research method uses normative juridical research. The results of the study show that the implications of the existence of Foreign Workers on efforts to improve justice and welfare of Indonesia's workforce are the filling of positions that local workers are unable to fill, the transfer of technology and expertise from foreign workers to Indonesia workers which is expected to be beneficial for Indonesia's workforce itself and help in terms of economic development of Indonesia because Foreign workers who come bring capital to be invested.